2013
DOI: 10.1186/2193-1801-2-589
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional therapy in luminal-like and HER2-enriched patients with de novo stage IV breast cancer

Abstract: BackgroundLocoregional therapy is rarely the standard of care for De Novo stage IV breast cancer but usually used for palliation of symptoms. This retrospective study aimed to determine whether surgery or radiation would contribute to survival benefit for this group of patients by examining the survival outcome through the disease molecular subtypes.Materials and methodsWe reviewed 246 patients with de novo stage IV (M1) breast cancer treated at our hospital between 1990 and 2009. Multivariable Cox Analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The authors reported that surgery was not associated with improved OS in patients with TN tumors, whereas it was associated with improved survival in patients with either HR or HER2-positive tumors when hormonal therapy and trastuzumab were used. Results were confirmed in other studies for patients with HER2positive tumors who received trastuzumab, and for those with HR-positive tumors (60,69,70).…”
Section: Superiority Of Tumor Biology Over Anatomic Dissemination For...supporting
confidence: 71%
“…The authors reported that surgery was not associated with improved OS in patients with TN tumors, whereas it was associated with improved survival in patients with either HR or HER2-positive tumors when hormonal therapy and trastuzumab were used. Results were confirmed in other studies for patients with HER2positive tumors who received trastuzumab, and for those with HR-positive tumors (60,69,70).…”
Section: Superiority Of Tumor Biology Over Anatomic Dissemination For...supporting
confidence: 71%
“…A study by Chen et al . found that local treatment including surgery or radiotherapy improved survival in patients with HR+/HER2- ( P = 0.0001) and HR±/HER2+ subtypes ( P = 0.0012), but survival did not improve in HR-/HER2- tumors after local treatment ( P = 0.9575) [ 19 ]. Neuman et al .…”
Section: Discussionmentioning
confidence: 99%
“…and Neuman et al . was only 45 and 35, respectively [ 19 , 20 ]. Therefore, we cannot conclusively establish the value of surgical intervention for HR-/HER2- patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were supposed to estimate the degree of survival advantage from surgery and chemotherapy for diverse-risk prognostic patients, which was conducive to the individualization in the evaluation of therapeutic efficacy. Chen et al [ 28 ] performed a retrospective study to evaluate the potential benefit of local treatment in 246 stage IV BC patients and found that local surgery or radiotherapy prolonged OS for Her2-positive (3-year, 41.6% vs 8.8%, p = 0.001) and luminal-like (3-year, 66.4% vs 34.4%, p <0.001) BC patients. Recently, Pons-Tostivint et al [ 29 ] conducted a large-scale multicentric retrospective study of 4276 de novo MBC patients, which concluded that locoregional surgery of the primary tumor would improve OS, except for patients with triple-negative molecular subtype.…”
Section: Discussionmentioning
confidence: 99%